Aggregate nitrogen dynamics in a plantation: simulated nitrogen deposition enhances mineralizable organic nitrogen transformation - Chen, Tian; Qi, Chuanxi; Liu, Can; Shu, Qianjuan; Si, Wanting; Cheng, Ruimei (Frontiers in Soil Science, 2025)
IntroductionArtificial Elevated atmospheric nitrogen (N) deposition enriches reactive N in terrestrial ecosystems, where soil organic nitrogen (SON) dominates the soil N pool. However, the composition of SON and its relationship with inorganic N remain poorly understood.MethodsTo assess the impact of N deposition on soil N dynamics under climate change, this study investigated a Quercus variabilis plantation in the Three Gorges reservoir area subjected to three years of N addition (0, 30, 60, 90 kg N ha-1 yr-1). Soil samples were sieved into four aggregate size fractions (8000–2000 μm, 2000–1000 μm, 1000–250 μm, <250 μm). Levels of acid-hydrolyzable nitrogen (AHN) and rates of net N mineralization (Nmin) and nitrification were measured.ResultsNet nitrification (0.30–3.42 mg N kg-1) comprised over 80% of net Nmin within aggregates.Net N transformation rates peaked in the finest soil aggregates (<250 μm), which exhibited the lowest available phosphorus (P) levels. These rates were positively correlated with N addition and microbial biomass. Total N and net N transformation increased with N input, while available P decreased. Multiple stepwise regression identified acid-hydrolyzable amino acid N, amino sugar N, and total AHN as effective predictors of net N transformation rates.DiscussionEnhanced N inputs significantly stimulated the conversion of SON into inorganic N, thereby amplifying soil N supply capacity. Nonetheless, prolonged N deposition raises concerns regarding potential phosphorus and soil organic matter loss.